Skybox image and video product evaluation. (2nd January 2016) - d'Angelo, Pablo; Máttyus, Gellért; Reinartz, Peter
ABSTRACT: Skybox Imaging launched the SkySat 1 and 2 satellites in 2013 and 2014. They are small and low-cost satellites, capable of recording still images with sub-metre resolution and high definition video for up to 90 seconds of a single target, using a novel focal plane with three 5.5 megapixel frame sensors. To improve resolution and signal-to-noise ratio of the still imagery, multiple frames are fused with super-resolution image merging. This article evaluates the SkySat image quality and georeferencing performance. For comparison, Worldview-3 (WV-3) data acquired over the same area is evaluated using the same procedure and reference data. Results show that georeferencing of SkySat still imagery products requires more ground control than other very high resolution sensors. Results from the Las Vegas video show that speed of moving vehicles in videos can be detected to better than 0.8 mph and that automatic motion detection can be used to georeference videos to street vector databases. Generation of digital surface models from video show a height accuracy of 1.2 m (NMAD).